ISOLATION OF ANTIOXIDANT COMPOUNDS OF METHANOL EXTRACT OF NUTMEG LEAVES (Myristica fragrans Houtt) - Nurmilasari Nurmilasari; Binawati Ginting; Hira Helwati (Universitas Syiah Kuala, 2017)
Abstract.The antioxidant activity from methanol extract of nutmeg leaves (Myristica fragrans Houtt) was performed using 2,2-diphenyl-1-picrylhydrazil (DPPH). Antioxidant assay using DPPH of the methanol extract at a concentration of 25 ppm, 50 ppm and 100 ppm, showed high antioxidant activity with IC50 = 36.31 ppm and Vitamin C showed antioxidant activity with IC50 = 3.657 ppm. The methanol extract of nutmeg leaves were partitioned with chloroform to obtain chloroform extract of the leaves with IC50 = 28.30 ppm. isolation of the active compounds from the chloroform extract of the nutmeg leaf using column chromatography yielded 6 mix fractions MFMD 1, MFMD 2, MFMD 3, MFMD 4, MFMD 5 and MFMD 6. The test results of antioxidant activity in very strong category is fractions MFMD 4, MFMD 3, MFMD 2, MFMD 6 and MFMD 5 with IC50 of each are 26.590 ppm, 27.239 ppm, 29.639 ppm, 39.766 ppm and 55.436 ppm, while antioxidant activity in a weak catagory is fraction MFMD 1 with IC50 is 126.270 ppm. This shows that the fraction of the leaf has a better inhibitory activity, because some of the active compound contained in the fraction can synergize in inhibiting free radicals, so that the IC50 value of the fraction is stronger than the extract. Keywords: Antioxidant, chromathography, Nutmeg (Myristica fragransHoutt), methanol extract, leaves